1997
DOI: 10.1149/1.1838081
|View full text |Cite
|
Sign up to set email alerts
|

Dechlorination of Monochlorobenzene Using Organic Mediators

Abstract: Dechlorination of monochlorobenzene using organic mediators ABSTRACTIn the presence of an organic mediator such as dibenzofuran, the reduction of chlorobenzene occurs indirectly and at substantially less negative potentials compared to its direct reduction at a glassy carbon cathode in acetonitrile. By using the indirect, mediator approach to reduction of chlorobenzene, constant current electrolysis at carbon plate cathodes can give complete dechlorination with high current efficiency Both divided and undivide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…14 The reduction of trichlorobenzene with dibenzofuran as mediator gives very similar results to those obtained with biphenyl as mediator. Here again, the trichlorobenzene concentration decreases rapidly and a large portion of the benzenes disappears.…”
Section: Mediated Electrolysis Of 124-trichlorobenzene-electrolysismentioning
confidence: 53%
See 2 more Smart Citations
“…14 The reduction of trichlorobenzene with dibenzofuran as mediator gives very similar results to those obtained with biphenyl as mediator. Here again, the trichlorobenzene concentration decreases rapidly and a large portion of the benzenes disappears.…”
Section: Mediated Electrolysis Of 124-trichlorobenzene-electrolysismentioning
confidence: 53%
“…This method has already been described in an earlier paper. 14 The result thus obtained for trichlorobenzene with phenanthridine as mediator is log k 3r2 ϭ 4.3. This rate of reaction is calculated assuming that trichlorobenzene is reduced via a two-electron transfer to dichlorobenzene and that the further reduction of dichlorobenzene can be neglected.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The major remediation method for more the accumulation of chlorobenzenes with a higher chlorination level in soils is incineration at high temperatures for digging out of soils. In the previous reports of electrochemical dehalogenation of chlorinated benzenes (Miyoshi et al, 2004;Mohammad and Dennis, 1997;Farwell et al, 1975;Kargina et al, 1997;Guena et al, 2000), the chlorine is eliminated step by step from the highly chlorinated benzenes to yield less-chlorinated benzenes and finally transform to benzene. Farwell et al (1975) reported on chlorobenzenes and the main cathodic reaction pathway for hexachlorobenzenes as follows: hexachlorobenzene → pentachlorobenzene → 1,2,3,5-tetrachlorobenzene → 1,2,4-trichlorobenzene → 1,4-dichlorobenzene → monochlorobenzene → benzene.…”
Section: Degradation Ability For Chlorinated Benzenesmentioning
confidence: 99%
“…However, such compounds are known to oxidize with concomitant fouling of the electrode surface. This leads to a rapid drop of the relevant electrochemical signal, which loses any proper analytical usefulness [4,5]. Thus a wide range of surface treatment and modification approaches have been used for the prevention of surface fouling and restoration of electrodes during detection of phenolic compounds [6 -8].…”
Section: Introductionmentioning
confidence: 99%